Pengaruh Intellectual Capital Dan Good Corporate Governance Terhadap Kinerja Keuangan Perusahaan Perbankan Yang Terdaftar Di BEI Periode 2019-2021 - Arif Firman Aulia; Endang Kartini; Herawati Khotmi (Lembaga Pengembangan, Penelitian dan Pengabdian Kepada Masyarakat (LP3M) Sekolah Tinggi Ilmu Ekonomi AMM (STIE AMM) Mataram, 2024)
This study aims to determine the effect of intellectual capital proxied by VAICTM and good corporate governance which is proxied by institutional ownership, independent commissioners and audit committees on company performance proxied by Return On Equity (ROE). The population in this study are banking companies listed on the Indonesia Stock Exchange in 2019-2021 using a purposive sampling technique using the criteria of banking companies issuing financial reports in 2019-2021 and banking companies earning profits in 2019-2021 so that a sample is obtained. 14 banking companies. The data analysis technique used in this study uses multiple linear regression analysis with SPSS Version 23. The results of this study indicate that partially intellectual capital proxied by VAICTM has an effect on company performance. Meanwhile, good corporate governance is proxied by institutional ownership, independent commissioners and audit committees that have no effect on company performance. The results of this study also show that the independent variables, namely intellectual capital and good corporate governance, are able to influence the dependent variable, namely company performance by 26.7% while the remaining 73.3% is influenced by other variables not used in this study.